2015
DOI: 10.1158/1055-9965.epi-15-0316
|View full text |Cite
|
Sign up to set email alerts
|

The Growing Burden of Endometrial Cancer: A Major Racial Disparity Affecting Black Women

Abstract: Background: In contrast with the decreasing incidence seen for most cancers, endometrial cancer has been increasing in the United States. We examined whether the increasing incidence and mortality from endometrial cancer are equally distributed by race/ethnicity and tumor histologic subtype.Methods: Surveillance, Epidemiology, and End Results (SEER) endometrial cancer incidence and mortality data were obtained from 2000 to 2011. Age-adjusted incidence and incidence-based mortality rates, 95% confidence interva… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
148
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(173 citation statements)
references
References 41 publications
6
148
4
1
Order By: Relevance
“…1,44,45 In addition, far less is known about their etiology. In a 2013 report from the Gynecologic Oncology Group trial, which included 2,244 type I endometrial cancers and 581 type II endometrial cancers from 62 U.S. institutions, type II endometrial cancer was positively associated with multiparity and smoking, and inversely associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,44,45 In addition, far less is known about their etiology. In a 2013 report from the Gynecologic Oncology Group trial, which included 2,244 type I endometrial cancers and 581 type II endometrial cancers from 62 U.S. institutions, type II endometrial cancer was positively associated with multiparity and smoking, and inversely associated with obesity.…”
Section: Discussionmentioning
confidence: 99%
“…1 After accounting for hysterectomy, black women have higher incidence rates of endometrial cancer than white women. 25 Black women are also more likely to be diagnosed with aggressive endometrial cancers (clear cell, serous, high-grade endometrioid, and malignant mixed Mullerian tumors) compared with non-Hispanic white women.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, one would expect Medicaid enrollment to have a greater impact on uterine cancer outcomes than cervical cancer outcomes, where screening availability outside Medicaid enrollment exists and which was the case in the current study. Uterine cancer disproportionately affects minority populations, with an increased incidence among black women, 16,17 and in low-income populations, it is commonly associated with advanced-stage disease at presentation. 18 These populations are especially vulnerable to adverse outcomes from this disease and may benefit from insurance coverage that allows for comprehensive examinations.…”
Section: Medicaid Enrollment Timing and Mortalitymentioning
confidence: 99%
“…Several studies reported significantly worse survival outcomes in AA DOI: 10.1159/000495613 women with EC compared to NAA women [4][5][6][7]. Disparities in outcome among AA women with EC do exist and continue to grow [8]. A higher prevalence of adverse prognostic factors in AA women such as advanced stage at diagnosis [4,9,10], higher tumor grade at diagnosis [9,10], lack of adequate access to healthcare [11], or combination of causes [12][13][14] have all contributed to this racial disparity in outcome.…”
Section: Introductionmentioning
confidence: 99%